Direct Cadmium Monitoring in Cigarette Filters Leachate by Molecular Fluorescence - Talio, María Carolina (2012)
This work proposes a new direct flourimetric methodology for cadmium traces quantification based on its association with azo-reagent SPADNS and rhodamine B dye. Experimental variables that influence on fluorimetric sensibility were optimized using uni-variation assays. The calibration graph using zeroth order calibration was linear from 0.192 to 1.26 104 ìg·L.1, with a correlation coefficient of 0.99. Under the optimal conditions, it was obtained a limit of detection of 0.057 ìg·L.1 and a limit of quantification of 0.192 ìg·L.1. The method showed good sensitivity, adequate selectivity with good tolerance to foreign ions, and was applied to the determination of trace amounts of cadmium in filters leachates coming from unsmoked, automatically smoked and smokers smoked cigarettes with satisfactory results. The proposed method represents an innovative application of luminescence to metal analysis comparable in sensitivity and accuracy to atomic spectroscopies.